2016
DOI: 10.1099/jgv.0.000331
|View full text |Cite
|
Sign up to set email alerts
|

FIG4 is a hepatitis C virus particle-bound protein implicated in virion morphogenesis and infectivity with cholesteryl ester modulation potential

Abstract: There is growing evidence that virus particles also contain host cell proteins, which provide viruses with certain properties required for entry and release. A proteomic analysis performed on double-gradient-purified hepatitis C virus (HCV) from two highly viraemic patients identified the phosphatidylinositol 3,5-bisphosphate 5-phosphatase FIG4 (KIAA0274) as part of the viral particles. We validated the association using immunoelectron microscopy, immunoprecipitation and neutralization assays in vitro as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The classical link between HCV lipo-viral particles and the association with VLDL assembly and release has been shown previously 21 . However, new pathways including the canonical endoplasmic reticulum-Golgi intermediate compartment, as well as the endosome-dependent pathway have been shown to be involved in HCV particle release 26, 27 . Hence, growing evidence supports the involvement of host proteins in viral entry, assembly, and release, and emphasizes the importance of targeting host proteins as a broad spectrum antiviral approach.…”
Section: Discussionmentioning
confidence: 99%
“…The classical link between HCV lipo-viral particles and the association with VLDL assembly and release has been shown previously 21 . However, new pathways including the canonical endoplasmic reticulum-Golgi intermediate compartment, as well as the endosome-dependent pathway have been shown to be involved in HCV particle release 26, 27 . Hence, growing evidence supports the involvement of host proteins in viral entry, assembly, and release, and emphasizes the importance of targeting host proteins as a broad spectrum antiviral approach.…”
Section: Discussionmentioning
confidence: 99%
“…The protein encoded by FIG4 belongs to the SAC domain-containing protein gene family. FIG4 binds to hepatitis C virus and modulates particle formation in a cholesteryl ester-related manner [63].…”
Section: Discussionmentioning
confidence: 99%
“…Other lipid-modulating host proteins that associate with viral particles have been identified. It was previously reported that the PI(3,5)P 2 5-phosphatase FIG4 is associated with viral particles [52]. Additionally, FIG4 deficiency impairs CE levels and HCV infectivity, whereas overexpression has the opposite effect, both without changing HCV RNA levels.…”
Section: Dress For Success-hcv Lipoviroparticle Formation and Egressmentioning
confidence: 93%